Aetiological factors of hoarseness of voice in patients attending at tertiary hospital Kashmir - Abbas, Syed Waseem; Naikoo, Javaid Ahmed; Maqsood, Reshaib; Nisar, Auqfeen; Ahmed, Rauf (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: Voice is an auditory perceptual term that means the audible sound produced by the larynx, which embodies such parameters as pitch, loudness, quality and variability. Hoarseness generally refers to a change in voice quality that may be manifested as a voice that sounds breathy, strained, rough, raspy, tremorous, strangled, or weak, or a voice that has a higher or lower pitch. The objective of the study was to evaluate the aetiological factors of hoarseness of voice. Methods: This is a prospective, non- randomized and longitudinal study conducted from July 2019 to July 2020 in department of Otorhinolaryngology of SMHS Hospital, Kashmir, India. All the patients with history of hoarseness underwent clinical examination, routine as well as special investigation to find out the diagnosis. The final results were analyzed by simple manual analysis with frequency and percentage using Microsoft Excel software 2007. Results: There were total 140 patients included in the study. Among them the age groups of 21 – 30 years and 31-40 years were mainly sufferers from hoarseness. Similarly, among 140 patients 100 (71.45%) were males whereas 40 (28.6%) were females with male to female ratio of 2.5. The most common cause as per the distribution was acid peptic laryngitis with frequency of 37.8% whereas papillary carcinoma of thyroid and papilloma of vocal cord accounts for only 0.4% each. Conclusions: There was etiological variation in hoarseness ranging from simple laryngitis to malignancies. So it is important not to ignore the hoarseness and precise history, examination and investigations should be done.